Different judgments about visual textures invoke different eye movement patterns (Journal of Eye Movement Research, 2010)
Top-down influences on the guidance of the eyes are generally modeled as modulating influences on bottom-up salience maps. Interested in task-driven influences on how, rather than where, the eyes are guided, we expected differences in eye movement parameters accompanying beauty and roughness judgments about visual textures. Participants judged textures for beauty and roughness, while their gaze-behavior was recorded. Eye movement parameters differed between the judgments, showing task effects on how people look at images. Similarity in the spatial distribution of attention suggests that differences in the guidance of attention are non-spatial, possibly feature-based. During the beauty judgment, participants fixated on patches that were richer in color information, further supporting the idea that differences in the guidance of attention are feature-based. A finding of shorter fixation durations during beauty judgments may indicate that extraction of the relevant features is easier during this judgment. This finding is consistent with a more ambient scanning mode during this judgment. The differences in eye movement parameters during different judgments about highly repetitive stimuli highlight the need for models of eye guidance to go beyond salience maps, to include the temporal dynamics of eye guidance.